2015
DOI: 10.1109/mcom.2015.7120028
|View full text |Cite
|
Sign up to set email alerts
|

Security vulnerabilities of connected vehicle streams and their impact on cooperative driving

Abstract: Abstract-Autonomous vehicle capable of navigating unpredictable real-world environments with little human feedback are a reality today. Such systems rely heavily on on-board sensors such as cameras, radar/LIDAR, and GPS as well as capabilities such as 3G/4G connectivity and V2V/V2I communication to make real time maneuvering decisions. Autonomous vehicle control imposes very strict requirements on the security of the communication channels used by the vehicle to exchange information as well as the control logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
196
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 339 publications
(196 citation statements)
references
References 15 publications
(18 reference statements)
0
196
0
Order By: Relevance
“…According to Petit and Shladover (2015), global navigation satellite systems (GNSS) spoofing and injection of fake messages into the communication between vehicles are the two most likely and most severe attacks for vehicle automation. Amoozadeh et al (2015) simulated message falsification and radio jamming attacks in a CACC vehicle stream, influencing the vehicles' acceleration and space gap, respectively. These researchers showed that security attacks could compromise traffic safety, causing stream instability and rear-end collisions.…”
Section: Literature Resultsmentioning
confidence: 99%
“…According to Petit and Shladover (2015), global navigation satellite systems (GNSS) spoofing and injection of fake messages into the communication between vehicles are the two most likely and most severe attacks for vehicle automation. Amoozadeh et al (2015) simulated message falsification and radio jamming attacks in a CACC vehicle stream, influencing the vehicles' acceleration and space gap, respectively. These researchers showed that security attacks could compromise traffic safety, causing stream instability and rear-end collisions.…”
Section: Literature Resultsmentioning
confidence: 99%
“…Similar to our work, previous work also identifies data spoofing as a realistic attack vector in the CV environment. Amoozadeh et al studied the V2V-based automated vehicle platoon system, and found that spoofed attacks can cause rear-end collision or significant instability [17]. A more recent work summarizes a comprehensive list of data spoofing attack sources including not only DSRC but also other sensors such as GPS [23].…”
Section: Related Workmentioning
confidence: 99%
“…() evaluated the impact of cyberattacks on freeway traffic using the optimal control and multiobjective optimization strategies; Amoozadeh et al. () investigated the effects of security attacks on the connected vehicle platoon by using VEhicular NeTwork Open Simulator (VENTOS) framework; and Dadras et al. () demonstrated that an attacker can cause the platoon to be unstable and even serious injury or death.…”
Section: Literature Reviewmentioning
confidence: 99%